Sandmeyer Trifluoromethylation - Danoun, Grégory; Bayarmagnai, Bilguun; Grünberg, Matthias F.; Matheis, Christian; Risto, Eugen; Gooßen, Lukas J. (Synthesis, 2014)
A range of benzotrifluorides are conveniently accessible in high yields from widely available (hetero)aromatic amines and the inexpensive trifluoromethylating agent TMSCF3 through a copper-mediated Sandmeyer trifluoromethylation reaction. Two practical procedures are presented. In the first, the diazonium salts are preformed in an extra reaction step, in the second approach the diazotization and the trifluoromethylation are combined into a one-pot procedure.
Keywords: anilines; copper; Sandmeyer reaction; trifluoromethylation; diazonium salts